NON-LINEAR SECTIONAL ANALYSIS OF REINFORCED CONCRETE COLUMN STRENGTHENED BY REINFORCED CONCRETE JACKETING WITH HIGH-STRENGTH STEEL - Imron Imron; Bambang Piscesa; Achfas Zacoeb (Journal of Civil Engineering, 2022)
This paper presents a nonlinear sectional analysis of reinforced concrete (RC) columns strengthened by RC jacketing, which also utilizes a high-strength reinforcing bar. A simple interface slip model was used to model the relationship between the old and the new concrete material. The initial axial load and bending moment are included in the analysis by introducing an initially prescribed strain before loading. The nonlinear sectional analysis was performed using an in-house MATLAB code utilizing the fiber-based method. The RC section was discretized with constant strain triangles (CST). The developed RC column model with jacketing was validated using the available test results in the literature. After the validation of the model was completed, the parametric study was carried out to gain an insight into the effect of using high strength reinforcing bar in the jacket structural element. The curvature and I10 ductility index were evaluated based on pure axial and constant axial loads with increased bending moment. From the validation of the model with the test result, the model predictions were satisfactorily showing a good fit, concluding that the developed MATLAB code can be used to evaluate RC columns strengthened with concrete jacketing. For the parametric study, the high strength reinforcing bar in RC column jacketing can increase the flexural, axial, and lateral load capacity but reduce the overall ductility. On the other hand, utilizing only high strength reinforcing bar for transverse reinforcement with tighter spacing resulted in higher ductility than if all the reinforcing bar was made from a high strength one.